Protective and Ameliorative Effects of Hydroethanolic Extract of Piper nigrum (L.) Stem against Antiretroviral Therapy-Induced Hepatotoxicity and Dyslipidemia in Wistar Rats - Doreen Enyang; Mubo A. Sonibare; Armelle D. Tchamgoue; Lauve R. Y. Tchokouaha; Fanta S. Yadang; Gael N. Nfor; Christelle W. Kom; Patrick D. H. Betote; Cedric F. Tchinda; Steveng S. K. Tiogo; Gabriel A. Agbor (Journal of Toxicology)
Antiretroviral therapy (ART) has revolutionized the lives of people living with HIV/AIDS by overall improving their quality of life and increasing life expectancy. However, ART-associated hepatotoxicity and metabolic disorders in HIV/AIDS patients are growing concerns to clinicians, especially due to the long-term use of the drugs. This study reported on the phytochemical and pharmacological profile of hydroethanolic extracts of Piper nigrum stem (PNS) and evaluated its protective effect against tenofovir/lamivudine/efavirenz (TLE)-induced hepatotoxicity and dyslipidemia in Wistar rats. Cytotoxic, antioxidant, and anti-inflammatory assays were performed on PNS. Thirty-six rats divided into 6 groups of 6 animals/group were administered: distilled water, 17 mg/kg TLE, 17 mg/kg TLE and 100 mg/kg silymarin, 17 mg/kg TLE, and Piper extract (200 mg/kg, 400 mg/kg, or 800 mg/kg) orally for 28 days. The body weight of animals was recorded every 7 days. On Day 29, the rats were sacrificed, and blood samples were collected for hematological and biochemical tests. Portions of the liver and kidneys were collected for histological evaluation, while liver homogenates were prepared from the rest to measure antioxidant enzymes. PNS possessed in vitro cytotoxic, antioxidant, and anti-inflammatory activities. A significant decrease p<0.05 in the body weight of rats treated with PNS was observed. A significant high platelet count p<0.05 was observed in the PNS800 mg/kg group. A considerable decrease in alkaline phosphatase and triglycerides was observed in the silymarin and PNS group compared to the TLE-only group. The findings also show a significant increase in catalase and glutathione in the TLE-only group compared to the normal group, while SOD decreased. Histological observations revealed normal hepatic and renal tissues in the silymarin, and PNS-treated groups compared to the normal control, while leucocyte infiltration was observed in the TLE-only group. These results suggest that PNS extract possessed antioxidant activity that alleviated TLE-induced toxicity. Further studies are necessary to understand the pharmacokinetic interactions between ART and PNS.